The genetic manipulation in our Peruvian legal system - Campos Barranzuela, Edhín (2008)
The genetic manipulation is in many cities of the world a new and controversial subject that has extreme importance not only for the Law and Medicine, but also for the whole society since the aspects derived from the procreation, ordering a child’s birth by artificial insemination changes a great part of the effective legal ordering. This development and evolution of the genetic practices has affected Peruvian people as well, for more than one decade has been realized techniques of attended human reproduction, artificial insemination and test-tube fertilization and now we also have the tools to make tests of identification through DNA, location of genes and we have banks of semen that satisfy demanding requirements and quality.